PENGARUH KARAKTERISTIK INDIVIDU DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. INFRACOM TECHNOLOGY JAKARTA PUSAT - Ervina Damayanti; Angga Juanda (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the influence of individual characteristics and work environment on employee performance at PT. Infracom Technology in Central Jakarta. The background of this study stems from the existence of work stress in individual characteristics and the suboptimal work environment, which are suspected to affect employee performance. The type of research used was quantitative research with an associative method. The population in this study was all 100 employees of PT. Infracom Technology in Central Jakarta. Data collection techniques were carried out by distributing questionnaires using a Likert scale, while data analysis was performed using SPSS version 26 software, which included validity tests, reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²). The results show that the career development variable (X1) has a positive and significant effect on employee performance, with a t-value of 5.633 > t-table = 1.984 and significance of 0.000 < 0.05. The work environment variable (X2) also has a positive and significant effect on employee performance, with a t-value of 3.515 > t-table = 1.984 and significance of 0.000 < 0.05. Simultaneously, both variables have a significant effect on employee performance with a calculated F value = 63.453 > table F = 3.09 and significance 0.000 < 0.05. The coefficient of determination value of 56.7% indicates that individual characteristics and work environment influence employee performance, while the remaining 44.3% is influenced by other factors. The results of this study emphasize the importance of continuous career development and a conducive work environment in improving employee performance at PT. Infracom Technology in Central Jakarta.